COMPARATIVE EFFECTIVENESS OF PREDNISOLONE PLUS CO-ENZYME Q10 VERSUS PREDNISOLONE ALONE IN THE TREATMENT OF BELL’S PALSY - Ali, Zafar; Afridi, Muhammad Abdur Rahman; Muhammad, Riaz; Asghar, Muhammad; Rahman, Syed Kashif Ur; Sebtain, Ali (Journal of Postgraduate Medical Institute, 2018)
Objective: To determine the comparative effectiveness of prednisolone plus co-enzyme Q10 versus prednisolone alone in the treatment of Bell's palsy. Methodology: This comparative clinical trial was carried out from March 18, 2017 to June 25, 2018. The study included 60 patients with Bell's palsy, above 18 years of age and either gender. Patients were selected by non-probability convenient sampling method. The study participants were randomized to either group 1 (prednisolone plus co-enzyme Q10) or group 2 (prednisolone alone). Effectiveness was calculated in terms of symptoms resolution and improvement in House-Brackmann (HB) grading scale in both groups. Chi square test was applied to compare the two groups. Results: There were 28 (46.7%) males and 32 (53.3%) females. Age of the patients ranged from 19 to 72 years with mean age of 34.90 ±14.99 years. Mean HB grade before initiation of treatment was 3.58 ±0.86, which improved to 2.18 ±0.98 after treatment. In group 1, mean HB grade improved to 2.23 ±0. 85 after treatment; while in group 2, it improved to 2.13 ±1.11 after treatment. Overall improvement was present in 50 (83.3%) of patients. In group 1, 90% patients and in group 2, 76.6% patients improved (p value 0.149). Conclusion: Significant improvement was observed in patients with Bell's palsy in both groups. Coenzyme Q10 based treatment was slightly better in terms of effectiveness, however, the difference was statistically not significant.